Усереднення початкової і багатоточкової задач для коливних систем із повільно змінними частотами і відхиленим аргументом - Самойленко, А.М.; Петришин, Р.І.; Данилюк, І.М. (Український математичний журнал, 2007)
New theorems on substantiation of the method of averaging over all fast variables on a segment and a
semiaxis are proved for multifrequency systems with deviated argument in slow and fast variables. An
algorithm for the solution of a multipoint problem with parameters is investigated and an estimate for the
difference of solutions of the original and averaged problems is obtained. Доказаны новые теоремы обоснования метода усреднения по всем быстрым переменным на отрезке и полуоси для многочастотных систем с отклоненным аргументом в медленных и быстрых переменных. Исследован алгоритм решения многоточечной задачи с параметрами и установлена оценка разности решений исходной и усредненной задач.